Worth every penny : build a business that thrills your customers and still charge what you're worth - Petty, Sarah (Greenleaf Book Group Press, 2012)
A revelation for small business owners: creating a profitable business is possible without getting into a slash-and-burn price war with your competitors. Petty and Verbeck inspire you to live your passion and pass your enthusiasm on to your customers, without succumbing to the pressure to discount.